A 15 year review of the causes of thoracotomy in Amirkola children's hospital - Soheil Osia; Rosemina Sadat Molaie; Abbas Hadipoor (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: A wide spectrum of pathologies can cause thoracotomy in the pediatric population. The aim of this study was to determine the frequency of causes of thoracotomy in Amirkola Children's Hospital. Materials and Methods: This cross sectional study was done on all patients that underwent thoracotomy in Amirkola Children's Hospital. All information was obtained from the patient medical records admitted between 2001- 2016. The causes of thoracotomy were considered. Results: Overall 60 patients were studied. Esophageal atresia type C with 37 cases (61.7%) was the most common cause of thoracotomy among children. In the study of associated diseases, 5 cases (8.3%) of patients suffered from Imperforate Anus. 44 cases (%88) of infants and only 6 cases (%12) of non-infants had congenital anomalies, and all 4 patients (100%) of non-infants had mediastinal masses. Five cases (83.3%) of non-infants and only one case (16.7%) of infants underwent thoracotomy because of infectious disease (p <0.001). No significant relationship was found between the causes of thoracotomy and gender (p = 0.41). Conclusion: Based on the results of this study, esophageal atresia type C is the most common cause of thoracotomy in infants. Additionally, congenital anomalies in infants and the mediastinal mass and infectious disease were more common in children.